PENDAFTARAN HAK ATAS MEREK - Asuan, Asuan (Faculty of Law, University of Palembang, 2022)
The right to a mark recognized by the Indonesian state is a brand that is a part of intellectual property rights as regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications, which revises Law Number 15 of 2001 concerning Marks which is a problem in research on how to register and protect rights to registered marks according to Number 20 of 2016 concerning Marks and Geographical Indications. This research is a normative legal research which is descriptive, not descriptive. Mark registration submitted by the applicant to the Directorate General of Marks, Ministry of Justice and Human Rights and the approved application (individual or legal entity) will receive a certificate registered in the general register of marks. the right to a registered mark is a legal protection of the exclusive right to use the mark yourself or to give permission to other parties to use the mark within 10 years from the date of receipt of registration and can be extended by the owner/or his legal representative.